Geneva Accord 1988: Its Repercussions for Afghanistan and Pakistan - Anwar, Salman; Ullah, Zakir; Irfan, Tayyab (The Lighthouse Journal of Social Sciences, 2024)
The Geneva Accord of 1988 marked a critical turning point in the Afghan conflict, bringing together the warring factions for negotiations that resulted in a comprehensive agreement. The accord outlined a series of provisions, including the withdrawal of Soviet forces from Afghanistan, the cessation of military aid to Afghan parties by external powers, the return of Afghan refugees, and a commitment to non-interference in Afghanistan's internal affairs. This historic agreement signaled the end of Soviet invasion in Afghanistan and raised hopes for a more stable and peaceful future for the war-torn country. The aftermath of the Geneva Accord had significant implications for Afghanistan and Pakistan. The Soviet Union withdrew its troops from Afghanistan by February 15, 1989. Although it ended its direct military involvement in the conflict but the accord did not bring immediate peace to Afghanistan. Instead, it left a power vacuum and a deeply divided country, as various Mujahideen factions struggled for control of the Kabul government. The study aims to identify the loopholes in this historic accord which led to a superfluous civil war in Afghanistan.